Luteoma of pregnancy. A case report - Asencio Aguedo, Angélica Yeyli (2018)
Luteoma of pregnancy is an infrequent non-neoplastic pathology of the ovary. It is usually an incidental finding during the evaluation of a pregnant patient in the third trimester or during a cesarean section. Occasionally, it may raise suspicion of cancer, resulting in unnecessary surgical resection of the ovary. We present the case of a 34-year-old woman who was in her third pregnancy and during the cesarean section, a 9 cm tumor of the right ovary was incidentally found and resected. The histological study was compatible with luteoma of pregnancy.